INTERNATIONAL EXPERIENCE OF REVITALIZATION OF INDUSTRIAL FACILITIES: OPPORTUNITIES FOR UKRAINE (Development Service Industry Management, 2024)
The changing conditions of economic activity in the modern business environment, large-scale international crises and the transformation of production processes have led to a decrease in the number of large industrial enterprises worldwide due to their bankruptcy and liquidation, or, on the contrary, to further development and modernization. As a result of these processes, the number of abandoned buildings and industrial areas that have been decommissioned is gradually increasing in the world, and as a result of transformational processes in industry, these real estate objects are not being used and are gradually turning into ruins. That is why the experience of reusing former industrial areas through their revitalization is currently a relevant research area for the implementation of the international experience of the revitalization of industrial facilities in Ukrainian realities.The article examines the theoretical foundations and practical experience of foreign projects on the revitalization of industrial facilities in order to explore the possibilities of implementing this method of transformation of industrial facilities into Ukrainian realities. The authors considered the conditions for the emergence of the need for the revitalization of industrial facilities, highlighted the characteristic features of revitalization in comparison with other types of transformations of industrial facilities. Examples of successful industrial revitalization in developed countries are presented, factors of relevance and beneficial impact of the implementation of revitalization are investigated. A sequence of stages of the revitalization process of industrial facilities has been formed, with the selection of necessary actions and tools inherent in each stage. Factors determining the choice of an industrial facility for revitalization were studied. The Ukrainian experience in implementing the revitalization of industrial facilities is considered.
Keywords: revitalization; industrial facilities; urban planning; transformation; socio-cultural facilities; infrastructure